La ilusión de la Libertad El liberalismo revolucionario en la década de 1820 en España y América - Chust, Manuel; Marchena Fernández, Juan; Schlez, Mariano (Ariadna Ediciones, 2021)
The volume that the reader has in his hands (or on his screen) constitutes a selection of the studies presented at the international congress "1820. The Illusion of Freedom. Revolutionary liberalism in Spain and America in the 1920s ", held in Las Cabezas de San Juan and Seville in March 2020, as a way to reflect (and celebrate, of course) the bicentennial of the revolution that began the so-called Liberal Triennium Spanish. The anniversary functioned as an excuse to analyze relevant problems of the present. In this case, the congress returned to the links between a stagnant society, which had nothing else to offer, and one of the most important revolutions that took place in the Iberian Peninsula. This was done through the presentation of a set of investigations that addressed the economic, political, social and cultural aspects of the Spanish revolution of 1820, and that crossed the Ibero-American world in the first half of the 19th century. It was a collective effort, which we hope we have embodied in this compilation.